Pengaruh Kualitas Produk Dan Desain Produk Terhadap Keputusan Pembelian Skincare Shomethinc Bagi Mahasiswa Universitas Muhammadiyah Gresik - Nina Anggraini Anandah; Umu Afifah; Vindy Widia Agustianis (Economics and Digital Business Review, 2024)
In Indonesia, various skincare brands are starting to grow rapidly with various different variants for various users' skin needs. Somethinc is a local brand that has succeeded in penetrating the skincare industry, founded by Iren Ursula in March 2019. Somethinc products have a marketing strategy that attracts consumers from various circles. Product quality is important for all companies considering that the products produced can compete in the market. Product design itself is one of the main elements that makes consumers consider purchasing an item. This research was conducted to analyze product quality and product design in relation to purchasing decisions. research using Quantitative Causal data analyzed using multiple linear regression analysis which shows that product quality and product design have a significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions, and product design has a positive and significant effect on purchasing decisions.